MANAJEMEN PENDIDIKAN DALAM PENGEMBANGAN SUMBER DAYA MANUSIA PADA PONDOK PESANTREN DARUL ABROR NW ENJER KOPANG - Haerul Anam; Ishak Hariyanto (Mudabbir: Jurnal Manajemen Dakwah, 2020)
The success of a boarding school today cannot be separated from the applied management concept. To analyze field study data, researchers used a case study method. The case study method means that this research focuses intensively on one particular object which studies it as a case to explore from related systems. This study reveals that the application of management concepts in the Darul Abror Islamic Boarding School, NW Enjer Kopang, cannot be separated from the concepts of planning, organizing, actuating, planning (POAC). Planning (planning) which consists of short-term, medium-term, and long-term programs. Organizing (organizing), by organizing, namely the division of duties, functions, and authority to each coach in carrying out their duties in a structured and organized manner. Actuating (movement), in the context of movement which is carried out by providing motivation on the sidelines of learning that involves all elements such as Ibtida'iyah, Mts, MA. Controlling (supervision), from the aspect of supervision, all elements in the Darul Abror NW Enjer Kopang Islamic Boarding School are involved to provide supervision regarding all work programs, both in terms of program implementation errors, weaknesses, failures, and strengths.